PENINGKATAN KETERAMPILAN MENULIS LAPORAN PENGAMATAN MELALUI MODEL PROBLEM BASED LEARNING (PBL) SISWA KELAS V SDN 1 BLIMBING KARANGNONGKO KLATEN - Bari Setyawan B. P.; C. Indah Nartani (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2015)
Â Abstract: The purpose of this research is to describe improve the observation report writing skill through Problem Based Learning (PBL) model in fifth grade students of State Primary School of 1 Blimbing Karangnongko Klaten. The type of research is Classroom Action Research (CAR). Research conducted at fifth grade of State Primary School of 1 Blimbing Karangnongko Klaten academic year 2014 / 2015. The research subject was all of the fifth grade students amount 22 students. The object of research is the observation report writing skill through Problem Based Learning (PBL) model. This study was conducted in two cycles. The writer obtained the data from observation result, interview, document and test. The results showed an increase in the observation report writing skill through Problem Based Learning (PBL) model. It is proven on the first condition is 60,23. It means that the class achievement percentage is 31,82%. In the fist cycle, the class average mark is 66,36. It means that the class achievement percentage is 54,55%. In the second cycle, the class average mark became 78,18. It means that the class achievement percentage is 90,91%. The result of this research is Problem Based Learning (PBL) could improve students skill of observation report writing in fifth grade students of State Primary School of 1 Blimbing Karangnongko Klaten.Â